6(x+3)+(7*8)=104

Simple and best practice solution for 6(x+3)+(7*8)=104 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+3)+(7*8)=104 equation:


Simplifying
6(x + 3) + (7 * 8) = 104

Reorder the terms:
6(3 + x) + (7 * 8) = 104
(3 * 6 + x * 6) + (7 * 8) = 104
(18 + 6x) + (7 * 8) = 104

Multiply 7 * 8
18 + 6x + (56) = 104
18 + 6x + 56 = 104

Reorder the terms:
18 + 56 + 6x = 104

Combine like terms: 18 + 56 = 74
74 + 6x = 104

Solving
74 + 6x = 104

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-74' to each side of the equation.
74 + -74 + 6x = 104 + -74

Combine like terms: 74 + -74 = 0
0 + 6x = 104 + -74
6x = 104 + -74

Combine like terms: 104 + -74 = 30
6x = 30

Divide each side by '6'.
x = 5

Simplifying
x = 5

See similar equations:

| 12/3=x/3-28/3x | | 3x+3=(x+7) | | 6x-6=2(10x+4) | | 3-4x=1-1x | | x^2+2x-388=0 | | x+(x/5)+2(x/5)=165 | | 2(x+2)=4(x+3) | | x+8/4=12 | | 3x-7y=47 | | 3x+7y=23 | | 5x+10y+ax+2ay=0 | | 4(4-b)=3(2b+2) | | lnx+lnx+2=6 | | (-6v+4)(-4v+2)=0 | | x+52/x=17 | | 1x+-8=-2 | | 16xy+11y=0 | | 5s-4s=45 | | x+7/x=(6x+14)/7 | | 0.66p+12=0.33p+10 | | -10x=-29 | | x+7/x=6x+14/7 | | (-6n+2)(5n+3)=0 | | (5+b)/2=-11 | | -k/5=12 | | 3/(x-9)=5/(x-6) | | 3x+-2=-11 | | 3x+10=110 | | (3+a)1/2=5 | | 14.37x-1.1245+5.687=978.654 | | 3/x-9=5/x-6 | | x-3pi=5pi |

Equations solver categories